Cation‐Tuned Synthesis of Fluorooxoborates: Towards Optimal Deep‐Ultraviolet Nonlinear Optical Materials - Wang, Ying; Zhang, Bingbing; Yang, Zhihua; Pan, Shilie (Angewandte Chemie International Edition, 2018)
The development of new nonlinear optical (NLO) materials for deep‐ultraviolet (DUV) applications is in great demand. However, the synthesis of an ideal DUV NLO crystal is a serious challenge. Herein, three new alkali‐metal fluorooxoborates, AB4O6F (A=K, Rb, and Cs, and a mixed cation between two of them), were successfully synthesized by cation regulation. It is found that all reported compounds exhibit short UV absorption edges (<190 nm), and show second harmonic generation (SHG) responses ranging from 0.8 to 1.9 KH2PO4 (KDP). Interestingly, by judicious selection of the A‐site alkali‐metal cations, the arrangement of NLO‐active structural units is fine‐tuned to an optimal configuration, which contributes to large SHG responses. Cation control: Three new deep‐ultraviolet nonlinear optical materials with excellent optical properties, comparable to those of KBe2BO3F2, have been obtained by cation‐controlled synthesis.